Accomplishments: Raising awareness of human rights and developing skills in secondary school - Marchel, Ana Laura; Peluffo, Mercedes; Perez Roig, Paula (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Since the beginning of this century, international organisations together with local legislation have strongly recommended initiatives for education on Human Rights with the aim of deepening the exercise of democratic citizenship and respect for fundamental freedoms. In this context, this interdisciplinary project is designed for young teenagers with the objective of raising awareness and placing them in a position to exercise their rights and responsibilities. It integrates different areas of Language, History and Social Studies with Human Rights Education. The project uses authentic material and provides teachers and students with a significant context to promote and develop skills for communication and participation. In the end, students share their productions outside the classroom boundaries.